Actin Filaments and Myosin I Alpha Cooperate with Microtubules for the Movement of Lysosomes - Cordonnier, Marie-Neige (The American Society for Cell Biology, 2001)
An earlier report suggested that actin and myosin I alpha (MMIα), a myosin associated with endosomes and lysosomes, were involved in the delivery of internalized molecules to lysosomes. To determine whether actin and MMIα were involved in the movement of lysosomes, we analyzed by time-lapse video microscopy the dynamic of lysosomes in living mouse hepatoma cells (BWTG3 cells), producing green fluorescent protein actin or a nonfunctional domain of MMIα. In GFP-actin cells, lysosomes displayed a combination of rapid long-range directional movements dependent on microtubules, short random movements, and pauses, sometimes on actin filaments. We showed that the inhibition of the dynamics of actin filaments by cytochalasin D increased pauses of lysosomes on actin structures, while depolymerization of actin filaments using latrunculin A increased the mobility of lysosomes but impaired the directionality of their long-range movements. The production of a nonfunctional domain of MMIα impaired the intracellular distribution of lysosomes and the directionality of their long-range movements. Altogether, our observations indicate for the first time that both actin filaments and MMIα contribute to the movement of lysosomes in cooperation with microtubules and their associated molecular motors.